Web-Based Bullying Case Reporting Information System at Indonesian Schools in Kota Kinabalu, Malaysia - Kadek Ayu Puja Astuti; Mohd. Mandala Putra; Murni Murni; Bhavya Joshi (Yayasan Cendekiawan Digital Indonesia, 2026)
Bullying in migrant school settings presents particular challenges due to limited access to protection services, the sensitivity of reporters' identities, and weak case documentation mechanisms. This situation was observed at the Indonesian School in Kota Kinabalu (SIKK), Malaysia, which serves children of Indonesian Migrant Workers, where a manual reporting system tends to discourage reporters and delay follow-up. This community service activity developed a web-based bullying reporting system using a Rapid Application Development (RAD) approach, including needs assessment, UML modeling, application development, user training, and evaluation using Black Box Testing and a Likert-based questionnaire. Participants included students, educators/mentors, and school coordinators involved in the reporting process. Descriptive-analytical analysis was conducted of system functional data and user perceptions. The implementation resulted in an application that met specifications, with an average feasibility of 87.7% in the very feasibility category, indicating improved documentation regularity and transparency in the case-handling process. This implementation experience provides a conceptual contribution to educational technology-based community service practices by offering an adaptive digital reporting model for Indonesian schools abroad and in cross-border educational contexts, thereby expanding the global discourse on information system integration in student protection.